PENGARUH LABA, ARUS KAS OPERASI, ARUS KAS BEBAS, DAN PEMBAYARAN DIVIDEN KAS SEBELUMNYA TERHADAP DIVIDEN KAS YANG DITERIMA OLEH PEMEGANG SAHAM (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Muhammad Ridh Ramli; Muhammad Arfan (Jurnal Telaah dan Riset Akuntansi, 2011)
The objective of this research is to examine and analyze the influence of earnings, operating cash flow, free cash flow,  and last year cash dividend both simultaneously and partially toward cash dividend received by stock holders on listed companies from the manufacturing sector at the Indonesia Stock Exchange for the year 2001-2005. The research type used is verificative research by using census method.The target population of this research is listed companies from the manufacturing sector at the Indonesia Stock Exchange which have positive earnings, operating cash flow, free cash flow and pay cash dividend both current year and last year. After being selected, there are 11 companies as target population. Because this research is done for five years, the total observations are 55. The multiple regression model is used to examine the influence of earnings, operating cash flow, free cash flow, and last year cash dividend both simultaneously and partially toward cash dividend received by stock holders.The results of this research show that (1) earnings, operating cash flow, free cash flow, and last year cash dividend simultaneously have influence toward cash dividend received by stock holders, (2) partially, earnings, free cash flow, and last year cash dividend have positive influence toward cash dividend received by stock holders, whereas operating cash flow has negative influence toward cash dividend received by stock holders. Keywords: earnings, operating cash flow, free cash flow, and cash dividend